FAKTOR SOSIAL DAN PERSONAL YANG MEMPENGARUHI KONSUMEN MEMBELI BARANG FASHION TIRUAN (COUNTERFEITED FASHION GOODS) - Desyra Sukma Dewanthi (Bina Nusantara University, 2015)
In current time there are more rampant counterfeiting measures, both worldwide and in Indonesia. In addition to welfare, there are some social and personal factors that influence consumer attitudes towards fashion counterfeited goods. These factors are normative susceptibility, value consciousness, collectivism, and novelty seeking. Following study aimed to determine the dominant factors that influence consumer attitudes in Indonesia against counterfeited fashion goods which then also affect their willingness to purchase the product. In addition, this study was conducted to compare the attitude of buyers and non-buyers of the counterfeited fashion goods. Moreover, data collection was conducted through survey strategy by distributing a questionnaire to 126 respondents in several shopping malls in Jakarta. The data collected was then processed using several techniques, one of which was a regression analysis. The study results showed that only normative susceptibility and collectivism factors shown a positive influence on consumer attitudes on counterfeit fashion goods. The results will lead to the desire of consumers to buy counterfeited fashion goods.